2003
DOI: 10.1111/j.1349-7006.2003.tb01387.x
|View full text |Cite
|
Sign up to set email alerts
|

High susceptibility of the ACI and spontaneously hypertensive rat (SHR) strains to 2‐amino‐1‐methyl‐6‐phenylimidazo[4,5‐b]pyridine (PhIP) prostate carcinogenesis

Abstract: rostate cancer is the most common non-cutaneous cancer in men in Western countries such as Europe and the United States 1) and its prevalence has also been increasing in Japan, 2) concomitantly with change in life style. Androgen ablation therapy is widely accepted and carried out for prostate cancers because androgens are essential for the development and growth of normal prostate and prostate cancer cells.3) However, outgrowth of hormone-independent cancer cells occurs within 1-2 years and eventually leads t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 33 publications
(35 reference statements)
0
13
0
Order By: Relevance
“…Importantly, it has also been observed that the administration of high-fat stress diet to PhIP-treated CYP1A humanized mice promoted prostate carcinogenesis and formation of carcinoma in situ [22] . In the same pathway, the treatment of male Fischer rats with mutagenic heterocyclic amine PhIP in the diet for 20 wk also induced inflammation, post-inflammatory proliferative or glandular atrophy and PIN lesions in the ventral prostate that culminated to invasive carcinomas after a subsequent treatment of rats with testosterone propionate [23,34] . Hence, these in vivo data suggest a potential relationship between the induction of a persistent prostate inflammatory response and PC development.…”
Section: Inflammation and Pcmentioning
confidence: 92%
“…Importantly, it has also been observed that the administration of high-fat stress diet to PhIP-treated CYP1A humanized mice promoted prostate carcinogenesis and formation of carcinoma in situ [22] . In the same pathway, the treatment of male Fischer rats with mutagenic heterocyclic amine PhIP in the diet for 20 wk also induced inflammation, post-inflammatory proliferative or glandular atrophy and PIN lesions in the ventral prostate that culminated to invasive carcinomas after a subsequent treatment of rats with testosterone propionate [23,34] . Hence, these in vivo data suggest a potential relationship between the induction of a persistent prostate inflammatory response and PC development.…”
Section: Inflammation and Pcmentioning
confidence: 92%
“…ACI is susceptible to prostate carcinogenesis, and Wister, the original strain of BUF, is resistant (Isaacs 1984;Inaguma et al 2003). By linkage mapping with prostate cancers, we have recently mapped Pcr1 (chromosome 2), Pcr2 (chromosome 1), Pcs1 (chromosome 19), and Pcs2 (chromosome 20) (Yamashitaet al 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Here, we identified genes differentially expressed in the prostates of BUF/Nac (BUF) and ACI/N (ACI) rats that show different susceptibilities to prostate cancers (Isaacs 1984;Inaguma et al 2003). Loci responsible for different prostate cancer susceptibility in rats were recently mapped ( Yamashita et al 2005), and if differentially expressed genes or their controlling genes are present in the mapped loci, they are considered to be good candidates.…”
mentioning
confidence: 99%
“…The exposure of laboratory rats to dietary 2-amino-1-methyl-6-phenylimidazo [4,5-b]pyridine (PhIP) 66 results in carcinomas of the intestine in both sexes, in the mammary gland in females and in the prostate in males 65 . Rodent prostates contain four different lobes that do not correspond anatomically to the zones of the human prostate, and PhIP induces cancer only in the ventral lobe of rats 67 . In a recent study we exposed laboratory rats to PhIP and found a similar increase in the mutation frequency in all lobes of the prostate, yet the ventral lobe selectively responded with increased cell proliferation and cell death 68 .…”
Section: Dietary Factorsmentioning
confidence: 99%